Improving nutrition in Telangana: Insights from the current status of outcomes, determinants and interventions in 2016 - Mani, Sneha; Avula, Rasmi; Nguyen, Phuong Hong; Tran, Lan Mai; Menon, Purnima (International Food Policy Research Institute, 2017)
The purpose of this Policy Note is to examine the current status of undernutrition in Telangana and to document geographic variability in the major determinants of nutrition and the coverage of key nutrition and health interventions. In doing this analysis, we aim to highlight the key areas of action to improve nutrition in Telangana.